ACE2 and TMPRSS2 expression in patients before, during, and after SARS-CoV-2 infection - Grisard, Henrique Borges da Silva; Schörner, Marcos André; Barazzetti, Fernando Hartmann; Wachter, Julia Kinetz; Valmorbida, Manoela; Wagner, Glauber; Fongaro, Gislaine; Bazzo, Maria Luiza (Frontiers in Cellular and Infection Microbiology, 2024)
During the SARS-CoV-2 pandemic angiotensin-converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) were constantly under the scientific spotlight, but most studies evaluated ACE2 and TMPRSS2 expression levels in patients infected by SARS-CoV-2. Thus, this study aimed to evaluate the expression levels of both proteins before, during, and after-infection. For that, nasopharyngeal samples from 26 patients were used to measure ACE2/TMPRSS2 ex-pression via qPCR. Symptomatic patients presented lower ACE2 expression levels before and after the infection than those in asymptomatic patients; however, these levels increased during SARS-CoV-2 infection. In addition, symptomatic patients presented higher expression levels of TMPRSS2 pre-infection, which decreased in the following periods. In summary, ACE2 and TMPRSS2 expression levels are potential risk factors for the development of symptomatic COVID-19, and the presence of SARS-CoV-2 potentially modulates those levels.